THE EFFECT OF COOPERATIVE LEARNING MODELS: GROUP INVESTIGATION (GI) MODEL TOWARDS STUDENTS LEARNING RESULTS ON THE SUBJECT MATTER GAS KINETIC IN SENIOR HIGH SCHOOL 18 MEDAN SEMESTER II ACADEMIC YEAR 2016/2017 - Ayu Lestari; Mariati Purnama Simanjuntak; Wijayanti Wijaya (ISER (Indonesian Science Education Research), 2019)
This study aimed to determine the effect of using cooperative learning model which was Group Investigation (GI) model toward the student learning results on the subject matter Kinetic Theory of Gas Class XI Semester II Senior High School 18 Medan Academic Year 2016/2017. This kind of research was quasi-experiment with two group pre-test and post-test design. The population in research is all of students class XI Senior High School Negeri 18 Medan consists of 4 class. The sample of the research was taken by two classes determined by random sampling technique, that is class XI MIPA-2 using cooperative group investigation model type with number of students is 24 people and class XI MIPA-3 using conventional learning with number of students is 27 people. The research instrument in the form of an essay test was eight matter — data analysis techniques used by normality test, homogeneity test and different test (t-test). The results of data analysis there is the influence of cooperative learning model: group investigation type toward the resulting student learning on the subject matter Kinetic Theory of Gas in class XI Senior High School 18 Medan, Academic Year 2016/2017.Keywords: cooperative learning model type group investigation, the result of student learning, kinetic theory of gas